SYMBOLS, IDENTITY, AND MODERATION: A SOCIOLOGICAL PERSPECTIVE ON RELIGIOUS CULTURAL BRANDING BY RELIGIOUS LEADERS - Irwandi (GoAcademica Research dan Publishing, 2025)
This study explores the sociological meaning of religious cultural branding as practiced by religious leaders in the effort to foster religious moderation. Utilizing a qualitative approach rooted in the sociology of religion, the research examines how symbols, rituals, narratives, and visual representations are employed by religious figures to construct collective religious identities that emphasize tolerance, inclusivity, and peaceful coexistence. The study draws on theories of symbolic interactionism and identity construction to analyze how branding strategies are not merely tools of communication but also mechanisms of social influence and identity formation within religious communities. Data were collected through in-depth interviews with religious leaders, observation of public religious events, and content analysis of religious media. The findings suggest that religious cultural branding serves as both a symbolic and strategic medium for reinforcing moderate religious values, countering extremism, and negotiating religious authority in a pluralistic society. This study highlights the increasingly important role of religious leaders not only as spiritual guides but also as cultural communicators and agents of social cohesion.